PENDIDIKAN AGAMA ALTERNATIF: PEMBELAJARAN MELALUI PENGAJIAN BA’DA MAGRIB-ISYA DALAM PEMBENTUKAN AKHLAK ANAK - Mursyid Irfan (Jurnal Anak Bangsa, 2022)
Establish of Children's morality is very important in this modern day, especially for teenagers who are looking for identity, it is necessary to be equipped with Islamic knowledge. Here researchers are interested in alternative religion education studies after maghrib-isya for teenagers as an effort to equip and shape the youth character for the better. The purpose of this research is to: (1) Describe alternative religion education studies after maghrib-isya, (2) describing the internalization of Islamic values through the study of studies after maghrib-isya in forming juvenile morality in the neighborhood Tanggul RW.12 Desa Cimuncang Serang, (3) describes the impact of the studies after maghrib-isya in the youth of the neighborhood Tanggul RW.12 Cimuncang  Serang.  To achieve the above objectives, there is a qualitative research approach that is descriptive. Methods of collecting data through observation, interviews and documentation. To check the validity of data using triangulation. The results showed that: (1)  studies after maghrib-isya is one of the religious-based alternative education that plays a role in learning to read Qur'aan, worship and morality. The learning process is sometimes done after praying Maghrib until the entrance of prayer time. This studies after maghrib-isya aims to educate children with ethical and Islamic culture, in the neighborhood Tanggul RW.12, There are three places of study, namely in the Hall of Studies Riyadul Muta'alimin, House Ustadzah Maemunah and house Ustad Suryadi, (2) The implementation of this study discusses the material about reading the Qur'an, worship and morality by occasionally associate it with the theme needed by teenagers. While the use of methods applied in this study is by the method of lectures, question and answer methods, methods of habituation, giving transparency, and giving motivation, (3) The impact of these studies has made a positive impact on teenagers especially in shaping adolescent morality that is increasing in the better direction